2015
DOI: 10.1186/s13054-015-1047-x
|View full text |Cite
|
Sign up to set email alerts
|

Daily laxative therapy reduces organ dysfunction in mechanically ventilated patients: a phase II randomized controlled trial

Abstract: IntroductionConstipation is a common problem in intensive care units. We assessed the efficacy and safety of laxative therapy aiming to promote daily defecation in reducing organ dysfunction in mechanically ventilated patients.MethodsWe conducted a prospective, randomized, controlled, nonblinded phase II clinical trial at two general intensive care units. Patients expected to remain ventilated for over 3 days were randomly assigned to daily defecation or control groups. The intervention group received lactulos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Our findings were congruent with De Azevedo et al (19) who reported that laxative therapy enhanced the daily defecation for the mechanically ventilated patients. Also, these data was stressed by Van der Spoel et al (20) who mentioned that patients who received both lactulose and polyethylene glycol were defecating promptly and effectively than placebo.…”
Section: Constipation Occurrence Among Critically Ill Patientssupporting
confidence: 93%
“…Our findings were congruent with De Azevedo et al (19) who reported that laxative therapy enhanced the daily defecation for the mechanically ventilated patients. Also, these data was stressed by Van der Spoel et al (20) who mentioned that patients who received both lactulose and polyethylene glycol were defecating promptly and effectively than placebo.…”
Section: Constipation Occurrence Among Critically Ill Patientssupporting
confidence: 93%
“…We studied 396 out of 2037 (19%) patients admitted to ICU ( Fig. 1 and Table 1 intensive care stay of 6 (4-8 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]) days (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…The association of laxatives with shorter times to defecate is unsurprising and has been described [2,11,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, it was observed that preventing constipation improved multi-organ failure in critically ill patients (7). Therefore, it is important that evidence of the clinical effects of the treatment of constipation are accumulated to improve the care of patients.…”
Section: Discussionmentioning
confidence: 99%